2008
DOI: 10.1507/endocrj.k08e-191
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Black Thyroid Associated with Hyalinizing Trabecular Tumor

Abstract: Abstract. Black thyroid is an uncommon phenomenon of black pigmentation of thyroid parenchyma induced by chronic minocycline therapy. Thyroid tumors associated with black pigmented thyroid are rare. We describe here a 42-year-old woman with a black thyroid associated with hyalinizing trabecular tumor (HTT). The patient presented with a palpable left-sided thyroid nodule. She had taken minocycline for aphthous stomatitis and an oral ulcer for 9 years. The findings of fine needle aspiration biopsy and BRAF mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(56 reference statements)
1
0
0
Order By: Relevance
“…However, case 2 displayed a BRAF gene mutation, although histopathological and immunohistochemical findings were entirely compatible with HTA. A similar case demonstrating discrepant results was previously documented by Kang et al 12 They reported a case of black thyroid associated with HTA. In their case, the thyroid tumor showed typical histopathological features of HTA and characteristic membranous MIB-1 staining, whereas a BRAF mutation, which is specific to PTCs, was also present.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…However, case 2 displayed a BRAF gene mutation, although histopathological and immunohistochemical findings were entirely compatible with HTA. A similar case demonstrating discrepant results was previously documented by Kang et al 12 They reported a case of black thyroid associated with HTA. In their case, the thyroid tumor showed typical histopathological features of HTA and characteristic membranous MIB-1 staining, whereas a BRAF mutation, which is specific to PTCs, was also present.…”
Section: Discussionsupporting
confidence: 81%
“…In the frozen sections subjected to touch imprint or scrape smear cytology, two of the four cases were initially reported as PTC and one as MTC but the remaining one was "suspicious of a hyalinizing trabecular tumor, adenoma vs carcinoma." 12 These results may be rare for this tumor and are not typical cytological features of HTA. One patient also had an occult papillary carcinoma in the opposite lobe of the thyroid, measuring 0.3 cm.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Similar findings have been observed in thyroidectomy specimens (Fig. 3 ), and in both benign and malignant thyroid nodules, pigmentation has been reported in all combinations: unpigmented nodule and pigmented thyroid parenchyma, pigmented nodule and pigmented thyroid parenchyma, and, rarely, pigmented nodule and unpigmented parenchyma [ 20 – 27 ].
Fig.
…”
Section: Antibioticssupporting
confidence: 85%